Combining production with preservation : livelihood strategies and innovations on nature pasture based farms in Dalsland, Sweden - Ortman, Tove (SLU/Dept. of Urban and Rural Development, 2018)
Biodiversity loss is a global problem that can lead to serious consequences. One of the most biodiverse habitats today is the product of extensive agriculture: semi-natural pastures, often termed High Nature Value (HNV) pasture. As farms become more and more intensive and specialised, these pastures disappear increasingly. This study aims to investigate how farmers can combine conservation of HNV pastures with profitable farming. In a qualitative case study in northern Dalsland, Sweden, ten pasture-based farms with HNV pastures have been studied. The case-study was conducted as a part of an action-oriented research and extension project, HNV-Link. The interview study has been complemented by participant observations at six visionary workshops about the future and background for HNV pastures with local actors in Dalsland. By applying a Sustainable Livelihood analysis, eight different types of activities and innovations were identified that supported the farmers’ Livelihood strategies, together with resources and social factors that influenced and inspired the farmers in forming the strategies. The farmers’ own motivation and values concerning the farm was an important factor, and three types of value orientation were used to discuss the differences: economical, traditional and ecological value orientation. Social networks with other farmers, either local or in other contexts, played an important role in spreading innovations and new ideas on how strategies could be formed to suit HNV pasture production, ideas that were later adapted to the specific conditions of the farm. Innovations and ideas for new entire strategies could come either from outside, from market initiatives or agricultural science, or from the farmers themselves. Depending on the outward and inward factors, the farmers innovated or adopted innovations that suited their farm. Important livelihood supporting activities and innovations were those related to utilizing pasture growth, diversifying the farm and using market solutions to receive payment for the ecological values of the production.